PERFORMANCE VISUALIZATION OF URBAN SYSTEMS - Johansson, Tim (Luleå tekniska universitet, Industriellt och hållbart byggande, 2017)
The planning, construction, management and use of our built environment are affected by diverse social, economic and environmental factors. Sustainable urban development is dependent on the understanding of the complex relations between the built environment, the social activities that take place over time and the interaction with the natural environment. The challenge to understand urban systems on both the local and global scale has inspired researchers and national agencies to develop sustainability indicators to support the planning, construction, management and use of the built environment. Access to open data of our built environment in national, regional and local databases opens new possibilities to generate models of our urban systems to facilitate visualization and analysis of indicators in order to enhance awareness of sustainability dimensions. Here spatial Extract, Transform and Load (ETL) technologies can be used in combination with Geographic Information system GIS to manage data sets from multiple sources in different formats. The purpose of this research is to investigate how spatial ETL technologies can be used to develop models in order to analyse and visualize the performance of urban systems. The applied method is grounded in system development and based on an abductive research approach that was repeated in six studies. Three of the studies deal with the relocation of Kiruna where models of the city was created and used to investigate the impact of mining subsidence on energy supply, infrastructure and buildings. The fourth case investigates the selection of insulation material on the embedded energy in a passive house in Kiruna. In the fifth case an urban model of the twin towns Malmberget/Gällivare was created to explore and relate data on attitudes from a survey to public data on population, infrastructure and built environment. The final case is the development of an energy atlas containing 90% of the multifamily building stock in Sweden. The atlas combines the energy performance and ...